2021
DOI: 10.1021/acscatal.0c05394
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Catalyzed [3 + 2] Annulation, Carbenoid Transfer, and C–H Insertion Cascade: Elucidation of Annulation Mechanisms via Benzopyrylium Intermediates

Abstract: It has been established that a cationic gold(I)/PCy 3 complex catalyzes the intramolecular cascade reaction of enediynecarbonyls via benzopyrylium intermediates giving pentacyclic compounds, bearing five or six stereocenters with high yields and diastereoselectivity. In this cascade reaction, [3 + 2] annulation, carbenoid transfer, and C−H insertion proceed in one-pot. The DFT calculation revealed that both the [3 + 2] and [4 + 2] annulations proceed via the same gold(I) carbenoid, produced by the [3 + 2] cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…From a synthetic perspective, this transformation will deliver highly sp 3 -rich polycyclic spiroether scaffolds, which are ubiquitous structural motifs in various bioactive compounds and drugs of natural origins. [48][49][50][51][52][53][54][55][56][57] We performed computational studies to determine the ET (∆G(T1-S0) = 53.6 kcal/mol) for substrate (Z)-1 (Table S13). It offers valuable guidance for choosing an appropriate photocatalyst among the myriad of available options.…”
Section: Resultsmentioning
confidence: 99%
“…From a synthetic perspective, this transformation will deliver highly sp 3 -rich polycyclic spiroether scaffolds, which are ubiquitous structural motifs in various bioactive compounds and drugs of natural origins. [48][49][50][51][52][53][54][55][56][57] We performed computational studies to determine the ET (∆G(T1-S0) = 53.6 kcal/mol) for substrate (Z)-1 (Table S13). It offers valuable guidance for choosing an appropriate photocatalyst among the myriad of available options.…”
Section: Resultsmentioning
confidence: 99%
“…The authors found that the amine group on the right-hand benzene ring benefited 6-endo-dig cyclization via an electron-donating effect to generate naphthalenes (37) after isomerization and protodeauration. In addition, several important heterocycles (38)(39)(40)(41) were synthesized in a divergent manner from that of naphthalene derivatives (37). In 2022, Liu and colleagues reported a gold(I)-catalyzed 6-endo-dig cyclization of arylalkyne-enolethers (36) to construct 2-(naphthalen-2-yl)aniline derivatives (Scheme 10) [31].…”
Section: Aryne-enolether Substratesmentioning
confidence: 99%
“…The generality of the ring formation protocol was illustrated by the applicability of a diverse range of electron-rich dipolarophiles that included vinyl ethers, alkenes, alkynes, allenes, and cyclopropenes, and heterocycles such as benzofurans and isoxazoles, as well as electron-deficient enones (Scheme 1a). [2][3][4][5][6][7][8][9][10][11][12][13][14][15] The synthetic utility of the catalytic [3 + 2] and [4 + 2] cycloaddition reaction method was also demonstrated by its application in synthetic strategies for a number of bioactive natural products and functional materials of current interest. 2c,11,12 Despite these notable advancements, the reaction chemistry of a metal-bound benzopyrylium intermediate with two or more 2π cycloaddition partners involving or initiated by a [3 + 2] cycloaddition remains conspicuously rare.…”
Section: Introductionmentioning
confidence: 99%
“…5a,10a, 18 The proposed cascade ring formations comprise a regiodivergent pathway that is unprecedented in the reaction chemistry of metal-bound benzopyrylium intermediates and adds to an increasingly important facet of gold catalysis concerning ligand-controlled product selectivity. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The practical utility of the Au(I)-catalyzed methods were also demonstrated by their showing the late-stage modification of a series of structurally complex natural products and drug molecules.…”
Section: Introductionmentioning
confidence: 99%